Chapter 2 Med det danske U20 ishockeylandshold til VM - Henriksen, Kristoffer (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The present case study investigates stress and recovery of the Danish national under- 20 ice hockey players during a training camp and the following World Championship. The aims were to track their stress-recovery states longitudinally, and to map their main sources of stress and recovery. Methods included a survey, qualitative interviews and a coach diary. Results showed well-balanced stress-recovery states during the entire period, and the athletes stated that this positively affected their well-being, and performance. The athletes' perceived sources of stress and recovery were classified into organizational, social, personal and athletic, with the organizational decisions and strategies playing a major role in reducing unnecessary stress and providing a good setting for engaging in recovery. The results lead us to suggest that coaches and managers be very mindful of the potential influence of their decisions on the athletes' stress and recovery when preparing training camps and participation in major competitions."